The Effect of Character Education on The Academic Motivation of Students at State Vocational School 15 Bandung - Fauziah, Fitri Nurul; Budimansyah, Dasim; Hakam, Kama Abdul; Dahliyana, Asep; Kurniawaty, Imas (Dinasti Publisher, 2025)
Character education is a key pillar in fostering sustainable academic motivation amidst the challenges of moral degradation and low student engagement in vocational schools. This study aims to analyze the influence of character education on the academic motivation of students at State Vocational High School (SMK) 15 Bandung, focusing on the dimensions of responsibility, integrity, and discipline in the context of vocational learning. A quantitative approach was employed, utilizing an explanatory survey method with 397 student respondents from four expertise programs: Social Work, Hospitality, Culinary, and Visual Communication Design. Data were collected through a Likert-scale-based questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results showed that character education had a positive and significant effect on students' academic motivation. Character values ​​were proven to strengthen students' self-efficacy, learning persistence, and goal orientation through increased self-regulation and perceptions of educational responsibility. These findings confirm the principles of self-determination theory and social-cognitive theory, which suggest that character-based learning can increase intrinsic motivation through the interaction between personal, social, and cognitive factors. This research makes theoretical contributions to the development of an integrative character-motivation model and offers practical implications for teachers and policymakers in designing learning experiences that foster student responsibility, independence, and overall well-being.